La obra paradoxográfica de Damascio (apud Phot. Bibl. cod. 130) - Ibáñez Chacón, Álvaro (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2008)
The codex 130 of Photius’ Library contains an extract from a lost work of the neoplatonic philosopher Damascius; this work is connected to the paradoxographic literature to the Imperial period and to the anthropological theme.